LIVE AND DRY DIETS FOR CURIMATÃ-PIOA (Prochilodus costatus) LARVAE - Mattos Pedreira, Marcelo; Epaminonda dos Santos, José Cláudio; Sá Fortes Pedreira, Rodrigo; Pelli, Afonso (Acta Biologica Brasiliensia, 2025)
Freshwater Neotropical fish larvae hatch with an immature digestive tract. Once they shift from endogenous to exogenous feeding, they undergo a critical period in which they still lack digestive enzymes and face difficulties capturing prey, making them susceptible to mortality. Therefore, this study evaluated the effect of different feeding regimes on Prochilodus costatus larvae. Five-day-old larvae were subjected to four feeding regimes: Artemia nauplii; powdered dry feed; plankton sieved through a 300 µm mesh (P300); and plankton sieved through a 300 µm mesh plus  dry feed (P300IF), in a completely randomized design with four treatments and three replicates each. Survival did not differ among diets. Larvae fed Artemia nauplii showed higher total length, weight, and biomass. Artemia nauplii were larger than wild plankton and provided greater biomass, increasing larval growth. Larvae fed dry feed and plankton plus dry feed showed similar performance for all parameters, demonstrating some capacity to assimilate dry feed. Larvae fed only plankton had a smaller total length than the other treatments, due to the lower plankton biomass, despite the number of prey per larva being the same as in the Artemia treatment. Thus, characterization of planktonic organisms is necessary to optimize feeding. Larvae showed the ability to ingest dry feed from the onset of exogenous feeding. However, this ability was limited, and live food remained essential, although future dry diets may be improved to meet larval requirements. Despite the limited assimilation of dry feed, when combined with live food, larvae grew more than those fed exclusively on plankton. In conclusion, larvae should be fed Artemia nauplii or other planktonic organisms providing adequate biomass and suitable prey characteristics to support growth. Further studies with dry feed are recommended.